Design of a Therapeutic Crane with Rehabilitation Monitoring for Patients with Reduced Mobility - Mendoza Diaz, Lenin Danilo (2021)
The present investigation has designed a therapeutic crane that helps patients who have lower body problems. As an alternative to the lack of equipment for physical rehabilitation, which leads to the reincorporation of people with reduced mobility to their activities of daily life, the objective proposed to solve the problem is the design and construction of a therapeutic crane with a system to monitor the rehabilitation process. The design and the solution were carried out based on the needs presented by the clinical areas in the implementation of rehabilitation technology that facilitates and promotes a better therapeutic process for patients. In addition, this therapeutic crane has functional duality, it is used for gait training with the support of the bodyweight that allows walking upright; as well as helping patients with cognitive impairment in the standing process; also, it has two vertical curved rails that help support the feet with hand restraints and offers a safe and functional environment, lifting a maximum weight of 180 kg of mass and a height of up to 1.95 m. The solution focuses on the construction of a square tube structure that forms an arch, has a handrail for holding the patient offering firmness and stability; providing the security of a device of reliability and easy handling; since it only requires an operator to monitor the process and an accessible environment for commissioning.